Molecular Profile of Cogongrass [Imperata cylindrica (L.) Raeusch] in Java Island Based on trnT(UGU)-trnL(UAA) IGS Sequences - Dwiati, Murni; Rahmah, Salma Auliya; Susanto, Agus Hery (Jurnal Biodjati, 2023)
Cogongrass is one of the top ten problem-causing weeds in the world that is invasively spread over many tropical and subtropical regions, including Java Island, the Republic of Indonesia. The wide distribution is possibly related to their adaptability to almost all terrestrial habitats from various altitudes, which may lead to a high level of genetic variation.Â  This study aimed to assess the genetic variation and phylogenetic relationship of cogongrass in Java Island using an intergenic spacer (IGS) sequence in the cpDNA genome, i.e. trnT(UGU)-trnL(UAA), as the molecular marker of high mutation rate. Plant samples were collected randomly from five different sites on the island. These were subjected to total genomic DNA extraction. The DNAs obtained were then used as PCR templates to amplify trnT(UGU)-trnL(UAA) IGS using a pair of universal primers. The PCR products were sequenced for genetic analysis. It was shown that an extremely high genetic variation with respect to the haplotype diversity of cogongrass in Java Island was observed. Nevertheless, a very low nucleotide diversity was obtained revealing a considerably close genetic relationship among the samples. Anatomical data regarding stomata number and length were found to correspond to the high level of genetic variation, but it was not the case with the stomata index.